Investigation of the Morenny rock glacier by geophysical methods (Journal of Geography and Environmental Management, 2024)
Global climate changes affect the ecological situation of mountain areas exposed to cryogenic processes. Currently, there are noticeable changes in the cryosphere of the mountains, and the risk of dangerous phenomena associated with the degradation of glaciers and permafrost is growing. One of the forms of mountainous relief is rock glaciers, which are formed in the zone of permafrost development and contain water in the solid phase. In a warming climate, rock glaciers can become sources of mudflow hazard, and the volume of ice contained in rock glaciers is an important resource for water reserves and plays a certain role in regional hydrological processes. According to calculations, there are 504 geomorphological formations in the Ile Alatau mountains. The article presents the results of a preliminary assessment of the structure of the Morenny rock glacier (Ulken Almaty River valley, Northern Tien Shan) using geophysical methods. Based on observational data from Kazhydromet at the Big Almaty Lake meteorological station, the climatic characteristics of the study area are given. It is shown that the average air temperature during the warm period increases at a rate of 0.1°C/10 years, the amount of precipitation for November-March increased slightly (observation period 1932-2022). Using electrical tomography methods (Skala-64 station) and electrical prospecting (Mala ground penetrating radar) it was possible to assess the structure of the frontal part and western lobe of the rock glacier. The results obtained indicate the presence of ice cores, established by high resistivity values. Zones of frozen rock-ice deposits and melt water-saturated areas were identified. Geoelectric and geological sections were compiled. The results of the studies confirm the earlier assumptions about the presence of large volumes of water accumulated in the body of the rock glacier.
Keywords: rock glacier, structure, geophysical methods, profiles, ice cores, rock-ice deposits.